Integra®-Dermal Regeneration Template and split-thickness skin grafting: a therapy approach to correct aplasia cutis congenita and epidermolysis bullosa in carmi syndrome - Trah, Julian; Haußer-Siller, Ingrid (Dermatology and therapy, 2018)
The association of junctional epidermolysis bullosa with pyloric atresia (JEB-PA) and aplasia cutis congenita (ACC) was described by El Shafie et al. (J Pediatr Surg 14(4):446-449, 1979) and Carmi et al. (Am J Med Genet 11:319-328, 1982). Most patients die in the first weeks of life, and no curative treatment options are available so far. We describe a patient with JEB-PA and ACC (OMIM # 226730) who was treated for extensive areas of ACC by Integra®-Dermal Regeneration Template and split-thickness skin grafting (STSG). Clinically, the dermal template changed into well-vascularized neodermis, and after STSG, full take of the transplants was detected. No infections of the huge ACC areas were seen. Further studies must validate this treatment option in severe and acute cases of JEB-PA with ACC. Based on clinical findings, we postulate that placement of Integra®-Dermal Regeneration Template with STSG could be a new treatment option for patients having JEB-PA with ACC to prevent severe infection, compartment-syndrome-like conditions, and deformities. Based on literature findings, we assume that Integra®-Dermal Regeneration Template with STSG could even be able to prevent new blistering and thereby be a treatment option in cases of ACC and JEB.
Gesehen am 14.05.2019
Nach "Integra" und vor dem Bindestrich ist hochgestellt ein "R" mit Kreis herum